Genetic influence on scar height and pliability after burn injury in individuals of European ancestry: A prospective cohort study. Issue 3 (May 2019) - Wallace, Hilary J.; Cadby, Gemma; Melton, Phillip E.; Wood, Fiona M.; Falder, Sian; Crowe, Margaret M.; Martin, Lisa J.; Marlow, Karen; Ward, Sarah V.; Fear, Mark W.
Highlights: Largest study to date on genetic variants associated with hypertrophic scarring. No individual genetic variants achieved the cut-off threshold of significance. Nervous system and cell adhesion gene pathways were associated with poor scar outcome. Abstract: After similar extent of injury there is considerable variability in scarring between individuals, in part due to genetic factors. This study aimed to identify genetic variants associated with scar height and pliability after burn injury. An exome-wide array association study and gene pathway analysis were performed on a prospective cohort of 665 patients treated for burn injury. Outcomes were scar height (SH) and scar pliability (SP) sub-scores of the modified Vancouver Scar Scale (mVSS). DNA was genotyped using the Infinium ® HumanCoreExome-24 BeadChip. Associations between genetic variants (single nucleotide polymorphisms) and SH and SP were estimated using an additive genetic model adjusting for age, sex, number of surgical procedures and % total body surface area of burn in subjects of European ancestry. No individual genetic variants achieved the cut-off threshold of significance. Gene regions were analysed for spatially correlated single nucleotide polymorphisms and significant regions identified using comb-p software. This gene list was subject to gene pathway analysis to find which biological process terms were over-represented. Using this approach biological processes related to the nervous system and cell adhesion were the predominant gene pathways associated with both SH and SP. This study suggests genes associated with innervation may be important in scar fibrosis. Further studies using similar and larger datasets will be essential to validate these findings.